The cooperative learning approach as a viable option in engaging tertiary students in online hypertext reading comprehension / Rasaya Marimuthu, Liaw Shun Chone and Lim Teck Heng - Marimuthu, Rasaya; Liaw, Shun Chone; Lim, Lim Teck Heng (Universiti Teknologi MARA, Kedah, 2014)
Among the boundless resources available to the ESL learners on the internet, the use of hypertext reading materials has necessitated that they employ different approaches to their language learning process. Cooperative learning (CL) is one such approach that has had a favourable effect in the traditional reading classroom. It would be a worthwhile effort to find out if the CL approach has the same effect on the learners in an online environment. Thus, the aim of this study was to find out if CL contributes towards better understanding of reading comprehension texts in terms of their reading score achievement and also their attitude towards the approach itself. The findings revealed that students showed improved achievement in their online hypertext reading comprehension scores compared to their counterparts from the non-CL group. It also showed that the CL students had better attitude towards this approach upon going through the activity. It can be deduced that online hypertext reading comprehension performance can be enhanced with the use of the CL approach. Hence, appropriately planned online reading strategy instruction with the infusion of the CL principles should be made an option so as to make the online reading experience of the students more rewarding.